Scotland, Renewable Energy and the Independence Debate: Will Head or Heart Rule the Roost?. Issue 1 (14th February 2013) - Toke, David; Sherry‐Brennan, Fionnguala; Cowell, Richard; Ellis, Geraint; Strachan, Peter
Abstract Political support for renewable energy development, especially offshore renewables, is particularly conspicuous in Scotland and is a centrepiece of SNP policy. However, this is built on something of a paradox because, put simply, without the subsidies paid by electricity consumers in the rest of the UK, the Scottish Government's ambitious targets for renewable energy would be politically unachievable. We argue in this paper that if Scotland does move towards independence, then there could be little reason for the UK to continue paying (much) of the subsidies since the resulting renewable generation would no longer contribute towards UK renewable energy targets. We suggest that the potential scenarios, and their implications, needs to be far better considered in the arguments around the Scottish constitutional position and the broader aims of UK energy policy.